Rejection of Rohingya in Aceh: The Role of Ulama and Tolerance in Acehnese Society - Yunus, Firdaus M.; Ikramatoun, Siti; Yasin, Taslim HM.; Abror, Robby Habiba (SCAD Independent, 2025)
The displacement of Rohingya refugees remains a pressing humanitarian issue, particularly in Aceh, Indonesia, where initial expressions of solidarity have shifted towards growing resistance. This study examines the factors driving this shift and the role of ulama in mediating social tensions amid economic anxieties and digital misinformation. Using a qualitative approach, primary data were collected through fieldwork conducted in Aceh between November 2023 and March 2024, including in-depth interviews with ulama, community leaders, and government officials, as well as document analysis. The findings reveal that while Aceh’s cultural and religious traditions emphasize hospitality, economic instability, resource competition, and misinformation have fueled skepticism toward continued refugee acceptance. Ulama, traditionally influential in shaping public discourse, face increasing challenges from digital narratives that undermine their authority and disrupt established mechanisms for building tolerance. This study highlights the urgent need for structured refugee policies, stronger cross-sectoral collaboration, and digital engagement strategies for ulama to maintain their influence. Without strategic interventions, Aceh’s long-standing reputation for tolerance may deteriorate, underscoring the importance of adaptive governance in refugee management.